Development and Validation of Prognostic Nomogram for Primary Peritoneal Serous Carcinoma Compared With FIGO Staging System: A Population-Based Study - Chen, Ming; Wen, Zhenzhen; Qi, Zhengwei; Gao, Min (Frontiers in Oncology, 2021)
Background: Primary peritoneal serous carcinoma (PPSC) is a rare tumor that lacks a prognostic prediction model. Our study aims to develop a nomogram to predict overall survival (OS) of PPSC patients. Methods: Patients confirmed to have PPSC between 2004 and 2012 were selected from the Surveillance, Epidemiology and End Results (SEER) database. LASSO and multivariate Cox regression analyses were used to screen for meaningful independent prognostic factors to construct a nomogram model for 3-, 5- and 10-year OS among patients with PPSC. The nomogram compared the discrimination, calibration and net benefits with the International Federation of Gynecology and Obstetrics (FIGO) staging system of PPSC paitents. Results: Eight variables were selected to establish the nomogram for PPSC. The established nomogram performed significantly better than the FIGO staging system (P < 0.05). The 3-year, 5-year and 10-year OS of PPSC was 0.498, 0.306 and 0.152, respectively. Patients of old age, widowed marital status, grade high, FIGO IIIB, IIIC, or IV, lymphnodes metastasis, no lymphadenectomy, no surgery and no chemotherapy got higher score which corresponds with higher risk and lower OS. In the multivariate Cox regression analysis, age, histological grade, FIGO staging, lymphnodes metastasis and lymphadenectomy (4 or more) were identified as independent prognostic factors for PPSC. Conclusions: PPSC patients have distinct characteristics with respect to their presentation and survival outcomes. A prognostic nomogram constructed by various clinical indicators can provide better and more accurate predictions for patients with PPSC.